Effect of Cr-doped on Crystalline Phase, Surface Morphology and Electrical Properties of Charge-Ordered Nd0.75Na0.25MnO3 Ceramics - Zawawi, Rabiatul Adawiyah; Khairulzaman, Nurul Nasuha; Shamsuddin, Suhadir (Journal of Science and Technology, 2017)
Nd0.75Na0.25Mn1-xCrxO3 (x = 0, 0.02 and 0.05) ceramics have been synthesized using solid-state reaction method and the crystalline phase, surface morphology as well as electrical properties were reported. Powder X-ray diffraction analysis revealed all samples showed single phase and crystallized in an orthorhombic perovskite-structure whose unit cell belongs to the space group of Pnma. The increment of Cr content influenced the lattice parameters and the calculated unit cell volume; this is suggested due to the difference of ionic radius between Mn3+ and Cr3+ ions. Scanning electron microscopy image for sample with x = 0 shown the grains was in irregular shape and inhomogeneous causing the grain boundaries was not clearly seen compared to the x = 0.02 and 0.05 samples. The temperature dependence of the electrical resistivity measurement for all samples showed insulating behavior down to lower temperature under zero magnetic field for all samples. However, analysis of resistivity data of dlnr/dT-1 vs T shows a peak around 210 K and 160 K for x = 0 and 0.02 samples respectively. No such peak has been observed for x = 0.05 sample. This may be an indication the charge-ordered (CO) state was weakened by Cr-doped.